Factors of Earnings Management: Empirical Study of the Main Board Consumer Non-Cyclicals Sector on the IDX for the Period 2020-2023 - Suci Sekar Melati; Eko Hariyanto; Sri Wahyuni; Edi Joko Setyadi (Innovation Business Management and Accounting Journal, 2025)
This study seeks to evaluate and analyze the factors influencing profits management in firms within the consumer non-cyclicals sector listed on the main board of the Indonesia Stock Exchange from 2020 to 2023. The research factors encompass free cash flow, profitability, audit quality, board of commissioners size, and board of directors. This study employs a purposive sampling method, yielding a sample of 33 companies from a research population of 40 companies. The four-year observation period resulted in 132 observations that met the research criteria. The analysis reveals that free cash flow, audit quality, profitability, and board of directors size have a significant effect on earnings management, while the size of the board of commissioners does not have a significant effect on earnings management.